Efficacy Outcomes of Endovascular Versus Surgical Revascularization in Critical Limb Ischemia: Results From a Prospective Cohort Study. (September 2018) - Schindewolf, Marc; Fuss, Torsten; Fink, Hanspeter; Gemperli, Armin; Haine, Axel; Baumgartner, Iris
Data on efficacy outcomes of endovascular versus surgical revascularization in patients with critical limb ischemia (CLI) in contemporary practice are limited. In this prospective cohort study, 353 consecutive patients with CLI were enrolled and allocated to endovascular (PTA [percutaneous transluminal angioplasty]), surgical (SURG), or no revascularization (No REVASC) after interdisciplinary consensus. Outcome measures were sustained primary clinical success (sPCS; survival without major amputation, repeated target extremity revascularization, and freedom from CLI), limb salvage, and amputation-free survival. Propensity-matched Kaplan-Meier analyses and stratified log-rank tests were performed. The PTA, SURG, and No REVASC groups consisted of 264, 62, and 27 patients, respectively. Compared to SURG patients, PTA patients were significantly older, had more risk factors, and more often had ischemic lesions. Propensity score-adjusted analyses showed no significant differences: sPCS was 51.3%/52.2%, limb salvage rate 91.5%/93.7%, and major amputation-free survival 90.5%/87.2% at 12 months for PTA and SURG, respectively. Amputation-free survival for the No REVASC group was 69% at 12 months. In conclusion, endovascular and surgical revascularization in CLI has comparable efficacy outcomes after 12 months. Contemporary overall outcome of patients with CLI is considerably better compared to earlier studies.